Conflict at the edge of the African state: the ADF rebel group in the Congo-Uganda borderland - Scorgie-Porter, Lindsay (Lexington Books, 2022)
An introduction to one of the world's most mysterious rebel groups -- A borderlands conceptual framework -- A burgeoning borderland in the Rwenzories -- Formations and consolidations, the ADF 1996-2003 -- Setbacks and recoveries, the ADF 2004-2013 -- Transformations or continuities? The ADF 2014-2021 -- Quelling conflict at the edge of the African state.